Bilingual Degree Teachers’ Beliefs: A Case Study in a Tertiary Setting - Johnson, Matthew (Pulso. Revista de educación, 2012)
Content and Language Integrated Learning (CLIL) is becoming ever more prominent in Spain as universities start to implement bilingual degree itineraries in response to the challenges of an increasingly globalised world. Currently, research into teachers beliefs in the field of bilingual education at university level is underrepresented and a fuller understanding of these beliefs could contribute towards the success of university CLIL programmes. This case study examines how the beliefs of five university lecturers involved in a bilingual project developed over the course of a two and a half year teacher training programme focusing on CLIL.